Multipeer connectivity in Xcode (Springer Nature, 2021)
Create a simple chat app for iOS using the Multipeer Connectivity framework. Multipeer Connectivity is an important development in the latest iOS. Using this framework, you'll provide users an interactive way to communicate and exchange data between each other. You'll see how to set one of the users as the host, and allow other users to join the hosted chat. Then each participant will be able to send a message in a shared room between all of the users. You'll achieve this by implementing the Multipeer Connectivity framework, setting up the room protocols, and creating pathways for the exchange of data with users in the room. Learn how to create multi-screen apps; save simple data, such as a person's screen name, indefinitely; and add a few storyboard elements, such as buttons and textfields. Finally, this video gives you a skeleton for creating other apps, such as a multiplayer game linked between different devices.